2021
DOI: 10.1097/01.aoa.0000796188.45232.98
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Management of Patients With Suspected or Confirmed COVID-19: Review and Recommendations for Perioperative Management From a Retrospective Cohort Study

Abstract: Perioperative management of patients with suspected or confirmed COVID-19. 1Recommendations based on a rapid review and retrospective cohort study of 2 outcomes in Tongji Hospital, Wuhan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
8

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 38 publications
1
4
0
8
Order By: Relevance
“…Moreover, these patients developed MAEs similar to those observed in individuals with isolated COVID-19 infection. Our findings are in accordance with those reported in a systematic review by Zheng et al, 18 which describes poorer safety outcomes for patients diagnosed with COVID after, rather than before, surgery. In our study, complication rates were greatest if a patient developed COVID-19 in the first month following a procedure, a finding similar to data from Price et al 21 Given that infection with SARS-CoV-2 in the 3 months following an operation conferred an increased risk of developing an MAE, it will be important to counsel and collaborate with patients, particularly those at greater risk for severe disease, 22 on vaccination and decisions surrounding timing of surgery in order to create the best individualized treatment plan.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, these patients developed MAEs similar to those observed in individuals with isolated COVID-19 infection. Our findings are in accordance with those reported in a systematic review by Zheng et al, 18 which describes poorer safety outcomes for patients diagnosed with COVID after, rather than before, surgery. In our study, complication rates were greatest if a patient developed COVID-19 in the first month following a procedure, a finding similar to data from Price et al 21 Given that infection with SARS-CoV-2 in the 3 months following an operation conferred an increased risk of developing an MAE, it will be important to counsel and collaborate with patients, particularly those at greater risk for severe disease, 22 on vaccination and decisions surrounding timing of surgery in order to create the best individualized treatment plan.…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review of 26 cohort studies examining surgical patients with perioperative COVID-19 found that emergency surgery, major surgery, and poorer preoperative condition were all risk factors for poorer safety outcomes. 18 In contrast, patients undergoing arthroscopy are often ambulatory and relatively active compared with surgical patients of other specialties. Since active patients are less likely to possess comorbidities (such as obesity, diabetes, and hypertension) known to confer an elevated risk of symptomatic and complicated SARS-CoV-2 infection, 19,20 it is not unexpected that arthroscopic sports medicine procedures would have fewer postoperative adverse events when compared with other surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…12 As per Zheng et al, studies that met the checklist with a score criteria of 80% or better were classed as high quality and those less than 80% low quality. 13 Key findings and emerging themes were collated to facilitate comparison of study design, intervention and outcome measures. A full systematic review and meta-analysis was not possible due to the heterogeneity of swallow measures and small number of studies.…”
Section: Data Extraction and Synthesismentioning
confidence: 99%
“…Dua faktor utama yang menyebabkan cedera sekunder adalah hipotensi (tekanan darah sistolik (TDS) < 90 mmHg dan hipoksemia (PaO 2 <60 mmHg). 14,15 Penanganan dalam periode perioperatif penting karena pembedahan dan anestesi membuat pasien rentan mengalami onset baru cedera sekunder, dan pada periode perioperatif juga, dapat dideteksi adanya cedera sekunder yang belum terdeteksi sebelumnya dan harus dikoreksi, untuk mencegah cedera otak sekunder yang baru dan memperbaiki luaran pasien. 2,14 Pencegahan cedera sekunder pada pasien dengan COVID-19 harus lebih diperhatikan karena adanya kemungkinan pasien sudah mengalami hipoksemia akibat ARDS.…”
Section: Diagnosis Covid-19unclassified
“…Pada pasien COT, oksigenasi harus dijaga dengn mempertahankan PaO 2 >100 mmHg. 15 Pada pasien COVID-19 terutama, oksigenasi sangat penting karena seringkali pasien mengalami hipoksemia akibat ARDS. Namun pada pasien ini, hasil AGD masih menunjukkan PaO 2 yang baik.…”
Section: Intraoperasiunclassified